Peningkatan Kesejahteraan Melalui Pengelolaan Keuangan Yang Bijak Untuk Hidup Layak - Meilani M; Misbahuddin M; Saleh Ridwan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Introduction to financial topics requires long study, specialization and in-depth study. Understanding the content and nature of economic theory is impossible except after thorough and in-depth study, observation and evaluation. This type of research is library research. Based on this discussion, it can be seen that Islam has an economic system that is fundamentally different from other economic systems. The Islamic economic system is rooted in Sharia, which forms a worldview, strategy and goals that are different from the secular system that prevails in the world today. A decent life is the dream and hope of every person living on this earth, of course every parent hopes for the welfare of their children and family in the form of material and spiritual prosperity, parents always try to fulfill their needs. Provide for his family, work hard, work hard, do anything to meet his family's needs, provide protection and comfort to his family from the various disturbances and dangers he faces.